Kecerdasan Emosi Ditinjau dari Compulsive Internet Use Pada Mahasiswa - Mawardah, Mutia; Dian Purnamasari, susan (Jurnal Ilmiah Psyche, 2024)
This study aims to investigate the effect of Compulsive Internet Use (CIU) on the emotional intelligence of students at Bina Darma University. Involving 100 randomly selected respondents, the study utilized the Compulsive Internet Use Scale (CIUS) to measure the level of compulsive internet usage and Wong and Law’s Emotional Intelligence Scale (WLEIS) to assess emotional intelligence. Data were collected through online questionnaires, and statistical descriptive and linear regression methods were employed for data analysis. The findings revealed that the majority of respondents (72%) experienced moderate to high levels of CIU, with an average CIUS score of 43.5 (SD = 9.8). Conversely, the respondents’ emotional intelligence was generally at a relatively good level, with an average WLEIS score of 88.2 (SD = 12.1). Regression analysis showed a significant negative effect of CIU on emotional intelligence (β = -0.36, p < 0.01), indicating that increased compulsive internet use is associated with lower emotional intelligence. These findings provide deeper insights into the impact of compulsive internet usage on the emotional well-being of students and emphasize the importance of interventions aimed at reducing excessive internet use to improve emotional intelligence.